Why Individuals Respond To COVID-19 Differently: A Battle of Sexes? - A., Olagunju Abdulrahmon; Lewis-Wade, Amanah (Journal of Medical Care Research and Review, 2020)
Several factors including genetic variations, cytokine storm (CS), macrophage activated syndrome (MAS), and lymphopenia have been recently discovered to influence the severity of COVID-19. Many studies have exclusively studied the pathogenesis of this disease, which includes the entry of the virus into the body, multiplication and spread, the progression of tissue damage, and the production of an immune response. However, questions like what makes some people more vulnerable than others to SARS-CoV-2 - the causative agent of the coronavirus disease; the role of gene networks in determining or influencing the efficiency of infection or the severity of COVID-19 symptoms are still in the valley of obscurity. What makes some SARS-CoV-2 infected individuals extremely sensitive to the development of acute respiratory distress syndrome (ARDS) while others are asymptomatic remains to be understood. Herein, we review the impact of a genetic variant in susceptibility and severity among sex and gender disparities, the significance of this variation in cases of severity and immune responses. Furthermore, we address major characteristics in severe COVID-19 cases, such as biochemical and homeostatic effects. For example, lymphocyte count and concentrations of inflammatory mediators within patients. Also, this paper identifies key clinical indicators of severe infections in the presence of cytokine storm and lymphopenia. Moreover, it takes into account predisposing factors that induce the severity of symptoms and underline the differences between mild and severe infections. Lastly, we explained the benefits of using bioinformatics to accelerate the progress made in COVID-19 research and future perspective in this research area.